What Are the Most Frequently Used Adjectives in Medical and Biology Articles Related to COVID-19? - Algharib, Munirah (Advances in Social Sciences Research Journal, 2022)
The present corpus-based study is devoted precisely to this aspect, investigating, specifically, which are the most used adjectives in a corpus of medical and biology texts dedicated to Covid-19 (CORD-19 corpus), and comparing the data obtained with a corpus of general scientific academic texts available on Sketch Engine (DOAJ corpora - Open Access Journals corpora- English), in order to verify any quantitative and qualitative differences in the frequency and use of qualifying adjectives in the two different text types.